Penerapan Permainan Musical Chair Untuk Meningkatkan Kemampuan Motorik Kasar Anak Kelompok B - Fadilatul Fitria; Fitta Nurisma Riswandi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
The background of this research is the problem of children's gross motor skills that are not well developed. Based on observations, it shows that 70% of children's ability to follow the teacher's simple movements is still not developed. It can be seen from (1) children are less enthusiastic about following movements and songs when exercising, (2) the lack of children's gross motor activities every day, (3) children rarely use gross motor game tools. This study used a classroom action research design (CAR) with 19 students in the B2 group of the Pembina State Kindergarten in Semarang City as the research subject. The data collection used is observation and documentation. This study used two cycles with 4 treatments in each cycle. The results showed that the teacher's activities in Musical Chair game obtained an average of 82.64 with very good criteria and children's activities reached 82.80% with very good qualifications. The level of enthusiasm of children in playing musical chair is 84.21%. Hence, it can be concluded that musical chair games can be an alternative for teachers to improve children's gross motor skills.